2014
DOI: 10.1007/s40820-014-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Joining of Individual Silver Nanowires via Electrical Current

Abstract: A procedure for joining polyol-synthesized silver nanowires in air using current-induced Joule heat welding is reported. Using a common probe station and photolithographically patterned gold electrodes, the welding process is completed using a common semiconductor analyzer. A unique two-step procedure eliminates the dielectric barrier at the point of contact without damaging the nanowires away from the junction. This procedure is designed for metal-metal contacts where a strong dielectric intermediate layer mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…This decrease in resistance may reveal material transformation to a state which facilitates filament style channels based on solid state diffusion from the initial composite material which forced electrical hopping internally. 16,19 Between 240℃ to 300℃, the increase in Ag nanowire ink resistivity is mainly due to broken nanowires 16 while at the same temperatures only a slightly increase of in-plane resistivity of Ag nanoplate ink was observed, likely due to oxidation. Again, Ag nanoplate inks demonstrate superior thermal stability than Ag nanowire inks.…”
Section: Electrical Properties Of Ag Nanoplate Inksmentioning
confidence: 95%
“…This decrease in resistance may reveal material transformation to a state which facilitates filament style channels based on solid state diffusion from the initial composite material which forced electrical hopping internally. 16,19 Between 240℃ to 300℃, the increase in Ag nanowire ink resistivity is mainly due to broken nanowires 16 while at the same temperatures only a slightly increase of in-plane resistivity of Ag nanoplate ink was observed, likely due to oxidation. Again, Ag nanoplate inks demonstrate superior thermal stability than Ag nanowire inks.…”
Section: Electrical Properties Of Ag Nanoplate Inksmentioning
confidence: 95%
“…Then the resulting sample was dried and washed in water to dissolve all the sodium-chloride, resulting in a porous block polymer sponge. [33] It is important to understand how the scale of these wires compares to the characteristic dimensions of the porous polymer-sponge structure. Next we cut sample into small rectangular strips, making it suitable for further mechanical testing.…”
Section: Fabrication and Morphological Characterizationmentioning
confidence: 99%
“…Among such techniques, joining of fine-scale materials is vital. Various techniques to join fine-scale materials, such as metallic or semiconducting nanomaterials (Kim, et al, 2005;Xu, et al, 2005;Tohmyoh, et al, 2007;Lu, et al, 2010;Tan and Wang, 2013;Peng, et al, 2013;Vafaei, et al, 2014;Ma, et al, 2016) and carbon nanotube (Hirayama, et al, 2001;Dong, et al, 2007;Jin, et al, 2007) have been reported. Electron beam (Xu, et al, 2005), laser beam (Kim, et al, 2005;Hu, et al, 2012;Dai, et al, 2016), or light (Garnett, et al, 2012) is used to melt a fine-scale materials for joining.…”
Section: Introductionmentioning
confidence: 99%